2013
DOI: 10.1371/journal.pone.0072779
|View full text |Cite
|
Sign up to set email alerts
|

Biogeography of Deep-Sea Benthic Bacteria at Regional Scale (LTER HAUSGARTEN, Fram Strait, Arctic)

Abstract: Knowledge on spatial scales of the distribution of deep-sea life is still sparse, but highly relevant to the understanding of dispersal, habitat ranges and ecological processes. We examined regional spatial distribution patterns of the benthic bacterial community and covarying environmental parameters such as water depth, biomass and energy availability at the Arctic Long-Term Ecological Research (LTER) site HAUSGARTEN (Eastern Fram Strait). Samples from 13 stations were retrieved from a bathymetric (1,284–3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
50
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(62 citation statements)
references
References 66 publications
(100 reference statements)
10
50
1
1
Order By: Relevance
“…Previous research has mainly focused only on the biogeographic patterns of microbial communities in surface sediments, both within ocean basins and globally, and this is discussed in detail in the Supporting Information (Schauer et al, 2010;Zinger et al, 2011;Bienhold et al, 2012;Jacob et al, 2013;Learman et al, 2016). In general, water depth appears to have more explanatory power within a region while geographic distance and carbon bioavailability tends to have more power in global studies (Zinger et al, 2011;Bienhold et al, 2016;Danovaro et al, 2016).…”
Section: Environmental Parameters Structuring Benthic Microbial Distrmentioning
confidence: 99%
“…Previous research has mainly focused only on the biogeographic patterns of microbial communities in surface sediments, both within ocean basins and globally, and this is discussed in detail in the Supporting Information (Schauer et al, 2010;Zinger et al, 2011;Bienhold et al, 2012;Jacob et al, 2013;Learman et al, 2016). In general, water depth appears to have more explanatory power within a region while geographic distance and carbon bioavailability tends to have more power in global studies (Zinger et al, 2011;Bienhold et al, 2016;Danovaro et al, 2016).…”
Section: Environmental Parameters Structuring Benthic Microbial Distrmentioning
confidence: 99%
“…In addition, this sampling effort was focused on a relatively small ocean region in comparison to similar studies, which provides both greater spatial resolution, while the focus on distinct regions in the Gulf of Mexico allowed for better generalization across the basin. One of the better studied regional ocean basins, with respect to biogeographic patterns in microbial community structure is the Arctic ocean (Bienhold et al, 2012;Jacob et al, 2013). Jacob et al (2013) used spatial variables similar to this study consisting of latitude, longitude, geographic distance, and water depth at the Arctic Long-Term Ecological Research (LTER) site to constrain microbial community variation in 13 surficial sediment samples collected along two transects.…”
Section: Environmental Parameters Structuring Benthic Microbial Distrmentioning
confidence: 99%
“…One of the better studied regional ocean basins, with respect to biogeographic patterns in microbial community structure is the Arctic ocean (Bienhold et al, 2012;Jacob et al, 2013). Jacob et al (2013) used spatial variables similar to this study consisting of latitude, longitude, geographic distance, and water depth at the Arctic Long-Term Ecological Research (LTER) site to constrain microbial community variation in 13 surficial sediment samples collected along two transects. Using redundancy analysis, Jacob et al (2013) found that bacterial community structure significantly varied with water depth and longitude (7% and 3% of the variance, respectively), while geographic distance was not significant.…”
Section: Environmental Parameters Structuring Benthic Microbial Distrmentioning
confidence: 99%
See 1 more Smart Citation
“…Diferentes profundidades do sedimento possuem diferentes condições ambientais e consequentemente a composição das comunidades microbianas muda com o aumento da profundidade no sedimento (JACOB et al, 2013;MEYER et al, 2013). Nesse trabalho foram analisadas apenas duas camadas de profundidade no sedimento (0-1cm e 1-4cm), em pequenas distâncias as espécies de micro-organismos conseguem dispersar ativamente entre os grãos do sedimento através da divisão celular, crescimento das populações e motilidade entre as partículas do sedimento, o que pode explicar a não influência da distância na estruturação das comunidades (LONG; AZAM, 2001).…”
Section: Distribuição Espacial Das Comunidades De Micro-organismos Nounclassified